Using Moodle as a Response System for higher education in Poland: Benefits and challenges - Bąkała, Anna; Molenda, Marek (Zastosowanie Moodle jako interaktywnego systemu odpowiedzi w kontekście edukacji wyższej w Polsce: zalety i wyzwania, 2020)
The paper explores learners’ responses to a new course format introduced in the Faculty of Philology at the University of Łódź. The course contained an interactive component with online tasks conducted in real time in the classroom. Instead of using dedicated Response Systems, we adopted Moodle LMS to verify whether it may be successfully used in that capacity. It may be concluded that despite its dated UI this system is still a viable option for offering interactive in-class instruction. The results of the student survey indicate that the course was well-received, although not all of its components were equally appreciated by the students. In particular, there was a significant difference between the reception of Open-Ended and Close-Ended questions. This difference might be explored from various perspectives, e.g. convenience vs learning effort or memorization vs acquiring skills The paper offers pedagogical implications which may help deal with the aforementioned problems
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 33-49
Keywords: informatyka ekonomiczna